KEVALIDAN MEDIA PEMBELAJARAN PRAKTIKUM SMART FALLING BALL MATERI AJAR SISTEM PERNAPASAN UNTUK PESERTA DIDIK KELAS XI MA NEGERI 2 SINJAI - Miftahul Khaeriyah; Saprin Saprin; Jamilah Jamilah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
Learning media is needed in the learning process and also in practicum activities. This research aimed to determine the validity of the learning practicum smart falling ball media in the respiratory system materials of class XI MA Negeri 2 Sinjai. This four-D research and development study consisted of defining, designing, developing, and disseminating stages. The research instrument used was the validation sheet. The results showed that the media was very valid, with an average score of 3.82. It implies that the learning practicum for smart falling ball media can continue in the field trial process.